Health Equity and Its Economic Determinants (HEED): Protocol for a pan-European microsimulation model for health impacts of income and social security policies - Srinivasa Vittal Katikireddi; Daniel Kopasker; Anna Pearce; Alastair H. Leyland; Mikael Rostila; Matteo Richiardi (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2022)
Introduction: Government policies on taxation and social security are important determinants of population health outcomes and health inequalities. However, there is a shortage of evidence to inform policymakers of the health consequences of such policies. The Health Equity and Its Economic Determinants project aims to assess the potential impacts of different taxation and social security policies across Europe on population health and health inequalities using a computer-based simulation that provides projections over multiple health domains. Methods and analysis: In the first phase, key input parameters for the model will be estimated using estimation techniques that control for the effects of prior exposure on time-varying confounders and mediators (g-methods). The second phase will involve developing and validating the microsimulation model for the UK. Policy proposals, developed with policymakers, will be simulated in the third phase to investigate the impacts of income tax and social security changes on population health and health inequalities. In the final phase, the microsimulation model will be extended across other European countries. Ethics and dissemination: This project will use deidentified secondary data for which ethical approval and consents were received by the original data collectors. No further ethical approval will be required for our main analytical datasets. Dissemination plans include academic publications, conference presentations, accessible policy briefings, mass media engagement and a project website. Both the syntax and the underlying synthetic data for the HEED microsimulation model will be made freely available through GitHub and the project website.
Keywords: 330; Income Dynamics; Microsimulation; Surveys; Psychology; Household Economics; Health; Taxation; Welfare Benefits; Economics; Well Being; Research